‘Neither a Toy nor a Comic Scene’: The Serious and the Humorous During the Independence of Chile, 1840-1840; [‘Ni Un Juguete Ni Una Escena Cómica’: Lo Serio y Lo Jocoso Durante la Independencia de Chile, 1810-1840] - Salinas-Campos, M (Universidad de Concepcion, 2023)
The Independence of Chile, as a crisis of the Spanish empire, was open to experiences of both seriousness and comedy, like any human expression. The elite felt compelled to impose strict discipline upon themselves and the entire population. This required limiting the comedic spirit of life. It was essential to meet the expectations of birthing a new nation in the Western world. The festive and humorous aspects of popular culture were discredited as expressions of barbarism that needed to be abandoned. The process of Independence became associated with compulsory military service, the press and its ideological warfare, political and religious intolerance—serious and fearsome aspects of life. Popular culture, on the other hand, continued to resist such civilizing seriousness. © 2023, Universidad de Concepcion. All rights reserved.